Automated Text-Level Semantic Markers of Alzheimer S Disease - Garcia-Serrano, A (WILEY, 2022)
IntroductionAutomated speech analysis has emerged as a scalable, cost-effective tool to identify persons with Alzheimer s disease dementia (ADD). Yet, most research is undermined by low interpretability and specificity. MethodsCombining statistical and machine learning analyses of natural speech data, we aimed to discriminate ADD patients from healthy controls (HCs) based on automated measures of domains typically affected in ADD: semantic granularity (coarseness of concepts) and ongoing semantic variability (conceptual closeness of successive words). To test for specificity, we replicated the analyses on Parkinson s disease (PD) patients. ResultsRelative to controls, ADD (but not PD) patients exhibited significant differences in both measures. Also, these features robustly discriminated between ADD patients and HC, while yielding near-chance classification between PD patients and HCs. DiscussionAutomated discourse-level semantic analyses can reveal objective, interpretable, and specific markers of ADD, bridging well-established neuropsychological targets with digital assessment tools.